2021
DOI: 10.3390/nano11030686
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy of Curved Surface Based on Lennard-Jones Potential

Abstract: Although various phenomena have confirmed that surface geometry has an impact on surface energy at micro/nano scales, determining the surface energy on micro/nano curved surfaces remains a challenge. In this paper, based on Lennard-Jones (L-J) pair potential, we study the geometrical effect on surface energy with the homogenization hypothesis. The surface energy is expressed as a function of local principle curvatures. The accuracy of curvature-based surface energy is confirmed by comparing surface energy on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Compared with an analogous nanotube system, SWCNTs, both BNNTs and hBN display significant hydrophilicity owing to their chemical structure . Especially, the curved surface of BNNTs is expected to have a higher surface energy than that of its planar analogue, hBN . Interestingly, however, recent experimental studies have reported the unusual hydrophobicity of BNNTs as opposed to hBN, which is largely hydrophilic. , This is caused by the inadvertent adsorption of airborne carbonaceous molecules, that is preferential to the curved surface of BNNTs, thereby lowering the apparent surface energy significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with an analogous nanotube system, SWCNTs, both BNNTs and hBN display significant hydrophilicity owing to their chemical structure . Especially, the curved surface of BNNTs is expected to have a higher surface energy than that of its planar analogue, hBN . Interestingly, however, recent experimental studies have reported the unusual hydrophobicity of BNNTs as opposed to hBN, which is largely hydrophilic. , This is caused by the inadvertent adsorption of airborne carbonaceous molecules, that is preferential to the curved surface of BNNTs, thereby lowering the apparent surface energy significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Uncertain geometry of protein/vesicle/cell/tissue surfaces impacts γ , within 5%. 203 Additional experiments on (de/at)tachment NPs aid assessment of tissue trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…K may increase/decrease via size-exclusion or immune response by aggrupation (clustering) of macrophages. Uncertain geometry of protein/vesicle/cell/tissue surfaces impacts γ, within 5% [203]. Additional experiments on (de/at)tachment NPs aid assessment of tissue trafficking.…”
Section: Outlook and Conclusionmentioning
confidence: 97%
“…They found that the surface energy increases in a concave surface and decreases in a convex surface relative to a flat surface. [132] Moreover, micro/nano-particles containing surfactants and light oils should also be taken into account to the floating dynamic due to its capability lowering water's surface tension. [133] 6.…”
Section: Floating Dynamicmentioning
confidence: 99%
“…studied this correlation through theoretical modelling of Lennard‐Jones potential intermolecular interaction between surface particles with surrounding particles. They found that the surface energy increases in a concave surface and decreases in a convex surface relative to a flat surface [132] . Moreover, micro/nano‐particles containing surfactants and light oils should also be taken into account to the floating dynamic due to its capability lowering water's surface tension [133]…”
Section: Floating Dynamicmentioning
confidence: 99%